The determinants of crowdfunding development - empirical analysis in the countries of Central and Eastern Europe - Joanna Bednarz; Magdalena Markiewicz; Agnieszka Ploska (Institute of Economic Research (IER), 2017)
Research background: Crowdfunding (CF) is a method of raising money for projects and enterprises by an online platform. Since around 2003 it is getting popular and becoming a natural method of pre-financing for start-ups before reaching out to investors. The estimations gave the scale of raising worldwide 35 bn USD via CF platforms in 2015. In 2016 CF was on track to surpass venture capital investments. Yet, this method doesn't progress equally worldwide and it is essential to find out what makes the difference of its development between the countries. Purpose of the article: The aim of the article is to examine the potential relation between: (1) the welfare of the countries, (2) structure of population and (3) availability of crowdfunding. The research is dedicated to the chosen countries of Central and Eastern Europe (CEE) in the period of 2005-2015, giving a perspective of changes in different terms of economy. Methodology/methods: This article, theoretical and empirical in character, is based on international desk research findings. The authors used methods of data collection, organizing and processing information. Moreover, they implemented methods of analogy and deduction, while studying papers, as well as the selection, analysis and synthesis methods. Findings: There is no direct correlation between GDP per capita of the country with it online alternative investments per capita. The richness of the country does not influence people willingness to invest money through online tools. In the countries of average level of welfare, alternative financing is used more widely. Moreover, there is a significant impact of the age structure of the population on the crowdfunding development. Estonia has the youngest structure of population and even there are not many inhabitants and the GDP per capita is average, the country has the most willing online crowd investors.
Keywords: G24; L26; M13; O16; O53; 330; crowdfunding; social funding; innovation; financing; CEE